Effects of Oral Care Protocol & Practices of Nurses on Oral Assessment Scores in the Ventilated Patients (International Journal of Nursing Care, 2020)
Purpose: The project aimed to examine the effects of an existing oral care protocol & practices of nurses onoral assessment scores in ventilated patients.Materials and Methods: Clinical data were collected during intensive care admission after 3 days ofimplementing an existing oral care protocol in Medical ICU. The Beck Oral Assessment Scale (BOAS) wasused to assess the oral cavity and to check the effectiveness of oral care provided by the nurses. Developedthe oral care education program consisted of instructions and a clear procedure outlining oral care. Data wasinput into and analyzed using Microsoft Excel.Results: The existing oral care protocol was found to be effective through the scores on BOAS. The findingsrevealed areas needs improvement in practices of nurses. The oral care education programme was plannedand presented to all nurses working in Medical ICU. Scores on the BOAS differed significantly before andafter educational intervention. Resources needed to carry out the protocol were identified and those wereprovided.Conclusion: Though the protocol of oral care is in place, there is always room for improvement. Oralassessment scores improved after reinforcement training as oral care practices were improved.
Keywords: Oral Care, Ventilated Patients, Medical ICU & BOAS.